On the polyconvolution with the weight function γ(y)=y of Hartley integral transforms H_1, H_2, H_1 and integral equations - Khoa, N. M.; Thang, T. V. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.5 We construct and investigate new polyconvolution with the weight function γ(y)=y of Hartley integral transforms H_1, H_2, H_1 and apply it to solve integral equations and a system of integral equations of polyconvolution type.